The mediating effect of knowledge-sharing behaviour on total quality management and organisational innovation capability - Buranakul, Sorapol; Limnararat, Sunpasit; Pithuncharurnlap, Manat; Sangmanee, Woranat (My University, 2017)
Ever since innovation was recognised as a key contributor to securing competitive advantage in the higher education arena, many factors have been introduced to enhance innovation capability. The purpose of this study is to examine the relationship between total quality management (TQM) and organisational innovation capability (OIC), as well as investigate the role of knowledge-sharing behaviour (KSB) in mediating this relationship. A survey was conducted on 367 academic staff and support staff from private universities in Thailand. The analytical results suggest that TQM is positively linked to OIC and KSB, in which the KSB plays a partial mediating role between TQM and OIC. The findings should benefit university administrators to improve innovation capability in addition to implementing TQM to develop appropriate strategies for maintaining a knowledge-sharing environment, leading to the kind of tacit knowledge that can successfully raise the innovation capability of private universities.
Keywords: Community of practice; Innovation capability; Knowledge sharing; Malcolm Baldrige National Quality Award; MBNQA; Mediating effect; Private university; Thailand; Total quality management; TQM